Appetence behaviours of the triatomine bug Rhodnius prolixus on a servosphere in response to the host metabolites carbon dioxide and ammonia - Otalora-Luna, F.; Perret, J. L.; Guerin, Patrick (My University, 2004)
A combination of 1,000 ppm CO2 plus 30-40 ppb NH3 in an air stream induced Rhodnius prolixus nymphs walking on a servosphere to perform a series of appetence behaviours. Shortly after the onset of stimulation the nymphs turned sharply upwind towards the source of the chemostimuli (within 13 +/- 9 s) from mostly downwind and crosswind walks in the air stream alone. The mean vector angles of these upwind tracks were concentrated in a cone 60degrees either side of due upwind. The upwind walking bugs stopped more frequently but for a shorter duration and walked at a higher speed than before stimulation. During stops in the presence of the chemostimuli the bugs frequently corrected their course angles and extended their forelegs to reach higher with their antennae in the air. In the air stream alone R. prolixus nymphs frequently sampled the sphere surface with the antennae and cleaned their antennae with the foreleg tarsi. However, the nymphs only briefly tapped the left or right antennal flagellum on the corresponding first leg tarsus and never touched the servosphere surface in the presence of the chemostimuli. After chemostimulus removal from the air stream the bugs continued to respond with the same appetence responses as during stimulation, but walked more tortuously in a crosswind direction in an effort to regain contact with the chemostimuli.
Keywords: rhodnius prolixus; triatomine bug; blood-sucking; behaviour; servosphere; orientation; infestans; hemiptera; beetles; breath; search; moths; cell